The effects of cognitive-motor dual-task training on athletes’ cognition and motor performance - Wu, Junyu; Qiu, Peng; Lv, Shuaibing; Chen, Mingxian; Li, Youqiang (Frontiers in Psychology, 2024)
Background: Cognitive-Motor Dual Task (CMDT) training has been widely utilized in rehabilitation and sports practice. However, whether CMDT training can better enhance athletes' cognitive-motor performance compared to traditional single-task(ST) training remains unclear.Method: A systematic review that complied with PRISMA was carried out (Prospero registration number: CRD42023443594). The electronic databases used for the systematic literature search from the beginning through June 13, 2023, included Web of Science, Embase, PubMed, and the Cochrane Library. After obtaining the initial literature, two researchers independently assessed it based on inclusion and exclusion criteria. Finally, the included literature was analyzed to compare the differences between ST training and CMDT training.Results: After screening 2094 articles, we included 10 acute studies and 7 chronic studies.Conclusion: This systematic review shows that athletes typically show a degradation of performance in CMDT situations as opposed to ST when evaluated transversally. However, this performance decline is notably reduced following longitudinal training in CMDT, indicating the effectiveness of sustained CMDT training in enhancing cognitive-motor performance under dual-task conditions. Our study provides new insights into the application of CMDT in the field of sports training. Practitioners can utilize CMDT to assess athletic skill levels or optimize cognitive-motor performance of athletes, taking into account the specific needs of each sport.